RUSSIA IN CENTRAL ASIA: A SHIFT TO POSITIVE FOREIGN POLICIES - RASHIDOV, Bakhtier (CENTRAL ASIA AND THE CAUCASUS, 2005)
Throughout the entire period of post-Soviet development, Russia has been harrowed by domestic problems: an entirely new distribution of political and economic power and the resultant reshuffling at the top; frantic efforts to bring remote regions, which imagined themselves “independent principalities,” into line; the war in Chechnia, etc. Some of the ministries, too, thought they were free to pursue their own policies uncorrelated with the RF Foreign Ministry. The Ministry of Atomic Energy, for example, put forward the initiative of selling nuclear reactors to Iran. Politicians remained locked in a fierce struggle for and against democratic principles; some of them even wanted to restore the great power approaches. For this reason, other states treated Russia with caution and resorted to preventive measures. On the other hand, this deprived Russia of a chance to pursue a more or less effective foreign policy. The evolution of Russia’s foreign policy approaches within the CIS is best illustrated by the notorious paper “SNG: nachaloili konets istorii” 1 (The CIS: the Beginning or End of History) and the recent statements by President Putin. The paper, authored by prominent political scientists Konstantin Zatulin and Andranik Migranian and permeated with imperial arrogance, said in part: “Only active measures (up to and including destabilization of the domestic situation in the regions, where anti-Russian and anti-integration forces have become especially obvious) can stem the process of a slow (and inevitable in the context of the current policies of Russia’s leaders) drift of these states away from Russia, which will turn the CIS into a nonentity… The Russian leaders have to clearly demonstrate to all their far and near partner-rivals that Russia would sooner encourage a large-scale redivision of the entire post-Soviet expanse by tapping all possibilities and the political sentiments of the Russian diaspora than permit the appearance of numerous anti-Russian centers of power resolved to oust it from the new abroad.” With the naïve conviction that destabilization would bring Russia political dividends, the authors elaborated their theory as applied to Ukraine, Georgia, Azerbaijan, and Central Asia. They failed, however, to take account of the other side of the coin: political and economic isolation; unacceptable direct confrontation with the Western and Islamic worlds, an economic crisis, involvement in numerous ethnic and political conflicts along Russia’s frontiers, and strong er separatist trends inside the country.